PENGARUH PENATALAYANAN MAJELIS JEMAAT TERHADAP PERTUMBUHAN SPIRITUALITAS MUDA-MUDI GEREJA HKI TAHUN 2019 - David Setya Siahaan (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2019)
Abstract - The purpose of this study was to determine the effect of stewardship of the Assembly of the Parish on the Growth of Spirituality of Young Men of the HKI Church in 2019. The method used in this study was quantitative inferential statistical research methods.  The results of data analysis show that there are positive and significant influences on the Assembly of Assembly Churches on the Growth of Spirituality of Young HKI Churches in 2019 as evidenced by data analysis as follows: Test of influence: a) Test the regression equation, obtained regression equation. b) Test the coefficient of determination of regression (r2) = 27.1%. c) Test the hypothesis by using the F test obtained Fcountat table ( Ftable ie 5.15 2.60 so H0 is rejected and Ha is accepted.Keywords: Stewardship of the Assembly of the Parish, Growth of Youth Spirituality